High sedentary behavior and low physical activity among adults in Afghanistan: results from a national cross-sectional survey - Supa Pengpid; Noormal, Ahmad Siyar; Peltzer, Karl (Frontiers in Public Health, 2023)
ObjectiveThe study aimed to evaluate the prevalence and correlates of sedentary behavior and combination of sedentary behavior and low physical activity among adults in Afghanistan in 2018.MethodsThis was a national representative cross-sectional study. The study utilized the data from Afghanistan STEPS survey 2018, where 3,956 adults (ages between 18 and 69 years) were interviewed at community-dwelling level. Using the Global Physical Activity Questionnaire, we have calculated the sedentary behavior and physical inactivity. Logistic regression was applied to investigate factors associated high sedentary behavior and low physical activity.ResultsApproximately half of the participants (49.8%) exhibited high levels of sedentary behavior, 40.3% low physical activity and 23.5% had both high sedentary behavior and low physical activity. Adjusted logistic regression analysis revealed that individuals who were employed (AOR: 0.34, 95% CI: 0.13-0.88) or self-employed (AOR: 0.60, 95% CI: 0.38-0.94) had significantly lower odds of both high SB and low physical activity than those whose work status was unpaid. Furthermore, older age (AOR: 1.75, 95% CI: 1.35-2.28), urban residence (AOR: 3.17, 95% CI: 1.72-6.05), having 4 or 5 adult household members (AOR: 1.77, 95% CI: 1.21-2.58) and being underweight (AOR: 1.78, 95% CI: 1.02-3.12) were found to be associated with high sedentary behavior. Moreover, factors such as female sex, having 4 or 5 or 6 or more adult household members, urban residence, overweight, and diabetes were positively associated, and male sex (AOR: 0.24, 95% CI: 0.12-0.51), being employed (AOR: 0.34, 95% CI: 0.13-0.88) or self-employed (AOR: 0.60, 95% CI: 0.38-0.94) were negatively associated with the occurrence of combination of high sedentary behavior and low physical activity.ConclusionHalf of the participants had high sedentary behavior, and one in four had both high sedentary behavior and low physical activity together. These findings emphasize the importance of targeted interventions aimed at reducing sedentary behavior and promoting physical activity, particularly among vulnerable populations such as females, individuals from lower socioeconomic background, urban residents, and those with chronic conditions. Addressing these factors can contribute to improving public health outcomes and reducing negative health impacts of sedentary behavior in Afghanistan.
Veröffentlicht: 19. September 2023
Gesehen am 07.11.2023